1994
DOI: 10.1007/bf00009839
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of the valid avian species of Haemoproteus, Leucocytozoon (Apicomplexa: Haemosporida) and Hepatozoon (Apicomplexa: Haemogregarinidae)

Abstract: The valid avian species of the apicomplexan blood parasite genera Haemoproteus, Hepatozoon and Leucocytozoon are arranged according to host family, assuming host familial specificity; salient points of the parasite morphology are recorded where appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 49 publications
0
28
1
1
Order By: Relevance
“…The measurements of the parasites in this study were not identical with those given for L. lovati by Sambon (1908) and Fantham (1910), but as pointed out by Bennett et al (1991) in their redescription of this species, these parasites are highly pleomorphic. The host cell was greatly transformed by the parasite in our samples.…”
contrasting
confidence: 63%
See 2 more Smart Citations
“…The measurements of the parasites in this study were not identical with those given for L. lovati by Sambon (1908) and Fantham (1910), but as pointed out by Bennett et al (1991) in their redescription of this species, these parasites are highly pleomorphic. The host cell was greatly transformed by the parasite in our samples.…”
contrasting
confidence: 63%
“…are hematozoan parasites that are transmitted by bloodsucking arthropods (Jordan, 1990). Currently, more than 60 species of Leucocytozoon have been detected from birds throughout the world (Bennett et al, 1994). Although it is rare that leucocytozoonosis is incriminated as a cause of death, it has been observed in some avian species, including waterfowl (Greiner, 1991), eagles (Stuht et al, 1999), and grouse (Clarke, 1935).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Classical taxonomic practice assumed a high degree of host specificity (Bennett and Peirce 1988;Bennett et al 1994), though some described species of Plasmodium are believed to infect hosts from various avian families on multiple continents (Bennett et al 1993). Recent molecular analyses of avian malaria parasites based primarily on mitochondrial sequences have revealed a wealth of genetic diversity among parasite lineages that is not apparent in their morphology (Bensch et al 2000;Perkins and Schall 2002;Ricklefs and Fallon 2002).…”
mentioning
confidence: 99%
“…Detection and description of Leucocytozoon species has been based on morphological analyses using microscopic observation of blood smears [3,6,13] which sometimes fails to detect the pathogen in cases of low parasitemia. Moreover, it has been suggested that there may be redundancy in the nomenclature of Leucocytozoon species [8].…”
mentioning
confidence: 99%